2000
DOI: 10.1111/j.1528-1157.2000.tb00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Epileptogenicity Correlated with Increased N‐Methyl‐d‐Aspartate Receptor Subunit NR2A/B in Human Focal Cortical Dysplasia

Abstract: Summary:Purpose: Human cortical dysplasia (CD) is a frequent cause of medically intractable focal epilepsy. The neurotransmitter mechanisms of epileptogenicity in these lesions have been attributed to changes in various glutamate receptor subtypes. Increased N-methyh-aspartate (NMDA) receptor (NR) 2A/B coassembled with NRI subunits hag been shown in focal epileptic CD. The purpose of this study is to correlate in situ CD epileptogenicity and the expression of various glutamate receptor subtypes.Methods: The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 14 publications
(23 reference statements)
4
75
0
2
Order By: Relevance
“…[28][29][30] In addition to the accurate definition, delineation of the boundaries of type I focal cortical dysplasia is also difficult, as the microscopically dysplastic lesion may extend well beyond the margins defined by the MRI-visible abnormality (in MRIpositive cases), [30][31][32] even with the use of highresolution dedicated epilepsy MRI protocols and review of the images by expert neuroradiologists. 26,32 Our finding of MRI-negative patients with hippocampal sclerosis is also consistent with previous literature that up to 30% of patients with hippocampal sclerosis may have normal findings on conventional MRI. 33 Surgical outcome of MRI-negative patients can be hard to determine due to heterogeneity of patient populations, surgical techniques, follow-up time, and outcome definition in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] In addition to the accurate definition, delineation of the boundaries of type I focal cortical dysplasia is also difficult, as the microscopically dysplastic lesion may extend well beyond the margins defined by the MRI-visible abnormality (in MRIpositive cases), [30][31][32] even with the use of highresolution dedicated epilepsy MRI protocols and review of the images by expert neuroradiologists. 26,32 Our finding of MRI-negative patients with hippocampal sclerosis is also consistent with previous literature that up to 30% of patients with hippocampal sclerosis may have normal findings on conventional MRI. 33 Surgical outcome of MRI-negative patients can be hard to determine due to heterogeneity of patient populations, surgical techniques, follow-up time, and outcome definition in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has suggested a link between the NR2A level and the symptomatic progression of this disease (Ali and Levine, 2006). An important role has been ascribed to NR2A/B subunits in human cortical dysplasia-induced epilepsy (Najm et al, 2000). The NR2B subtype has been implicated in Parkinson's disease (Nash et al, 1999) and in the mediation of nociception (Tan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence to suggest that balloon cells display intrinsic hyperexcitability, possibly because of a modification of N-methyl-d-aspartate receptors or decreased sensitivity of the γ-aminobutyric acid A receptors in these pacemaker cells. 10,18,19,31,32 In more diffuse cortical dysplasia, there may be abnormal connectivity of the cellular aggregate, which is associated with reorganization of cortical circuitry, and axons that would normally project out of the epileptic zone may also be interrupted and instead make excitatory synapses locally. These recurrent excitatory connections may cause feed-forward connectivity loops that drive the excitatory and consequent epileptic process.…”
Section: Volumetrics and Epileptogenesismentioning
confidence: 99%